2004
DOI: 10.1164/rccm.200303-346oc
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Oral Sildenafil and Beraprost Ameliorates Pulmonary Hypertension in Rats

Abstract: Sildenafil, an oral phosphodiesterase type-5 inhibitor, has vasodilatory effects through a cyclic guanosine 3', 5'-monophosphate-dependent mechanism, whereas beraprost, an oral prostacyclin analog, induces vasorelaxation through a cAMP-dependent mechanism. We investigated whether the combination of oral sildenafil and beraprost is superior to each drug alone in the treatment of pulmonary hypertension. Rats were randomized to receive repeated administration of saline, sildenafil, beraprost, or both of these dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
62
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 26 publications
(23 reference statements)
8
62
1
Order By: Relevance
“…As shown in Figure 4, the phosphodiesterase type V inhibitor sildenafil (5 mg/kg/day) did not show any significant inhibitory effects on RVSP, RV/(LV+S) and Lung/BW in monocrotaline-induced pulmonary hypertensive rats. Monotherapy with sildenafil (25 or 75 mg/kg/day) attenuates the elevation of pulmonary artery pressure and vascular remodeling in hypoxia-induced pulmonary hypertension [36], whereas combination therapy with sildenafil (25 mg/kg/day) and beraprost (100 µg/kg/day) attenuates the development of monocrotaline-induced pulmonary hypertension [37]. Sildenafil (100 mg/kg/day) was efficacious in rats with pulmonary hypertension, and the combination therapy of sildenafil and bosentan showed an additional effect for decreasing pulmonary arterial pressure, maintaining body weight, and reducing mortality [38].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4, the phosphodiesterase type V inhibitor sildenafil (5 mg/kg/day) did not show any significant inhibitory effects on RVSP, RV/(LV+S) and Lung/BW in monocrotaline-induced pulmonary hypertensive rats. Monotherapy with sildenafil (25 or 75 mg/kg/day) attenuates the elevation of pulmonary artery pressure and vascular remodeling in hypoxia-induced pulmonary hypertension [36], whereas combination therapy with sildenafil (25 mg/kg/day) and beraprost (100 µg/kg/day) attenuates the development of monocrotaline-induced pulmonary hypertension [37]. Sildenafil (100 mg/kg/day) was efficacious in rats with pulmonary hypertension, and the combination therapy of sildenafil and bosentan showed an additional effect for decreasing pulmonary arterial pressure, maintaining body weight, and reducing mortality [38].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, rats that received both a prostacyclin analog and a PDE5 inhibitor showed increased survival. 1 In summary, we present evidence for the first time that the prostacyclin analog UT-15C and PDE5 inhibitors interact to augment cAMP accumulation and ATP release from erythrocytes of humans with PAH. Some of the beneficial effects of the administration of these drugs in combination in PAH patients may be explained by the release of this potent vasodilator and stimulus for nitric oxide synthesis in the pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 72%
“…The mechanism underlying the augmented response with sildenafil and prostanoids is incompletely understood, but these findings suggest significant cross talk between the cyclic nucleotides. Itoh, et al 13) also demonstrated the additive effect of sildenafil and beraprost using an animal model of PAH.…”
Section: Discussionmentioning
confidence: 94%